Probability and statistics for engineers - Rao, Gajavelli. S. S. Bhishma (Scitech Pub, 2006)
Probability and statistics for engineers / Rao, Gajavelli. S. S. Bhishma. -- Kolkata: Scitech Pub., 2006 519.202 462 B575e3 3rd ed. No. of Copies : 1